(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of this research is to find out the procedures for managing Land and Building Tax in East Luwu Regency. This type of research uses qualitative methods. The data collection techniques used in this research were observation, interviews and direct documentation in the field. The informants in this research consisted of 5 people. The results of this research show that the East Luwu Regency Regional Revenue Agency has managed rural and urban land and building taxes based on 4 management functions, namely planning, organizing, implementing and supervising based on the main duties and functions of the agency. However, this cannot be said to be optimal in its management considering that there are several obstacles in the management of rural and urban land and building taxes, including that there are still many taxpayers who are not yet fully aware of the importance of paying taxes for regional development.